Development of Circulation System E-Dioclass to Foster Critical Reasoning and Cognitive Learning Outcomes - Farida Nuraini; Mimien Henie Irawati Al-Muhdhar; Zainudin Hassan; Murni Sapta Sari; Deny Setiawan; Cicilia Novi Primiani; Wachidatul Linda Yuhanna; Feni Tin Faizah (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2026)
Critical reasoning skills are still relatively low among students and have a significant impact on cognitive learning outcomes. This study aims to produce E-Dioclass learning media on the PBLPOE model of circulatory system material integrated with SDGs number 3 to develop critical reasoning dimensions and cognitive learning outcomes of phase F students that are valid and practical. The research model used is the Lee & Owens development model with five stages, namely analysis, design, development, implementation, and evaluation. The analysis stage aims to identify the needs of teachers and students. The design stage aims to design E-Dioclass media. The development stage is to realize the design in the form of a storyboard to become a prototype. The implementation stage is to apply the media in four meetings. The evaluation stage is to determine the effectiveness of the media. E-Dioclass media is a Google Classroom-assisted media that can be accessed online through electronic devices. The results of E-Dioclass media validation by media experts, material experts, and biology education practitioners obtained an average score of 95.7%. The results of the practicality test obtained a score of 81.6%. Therefore, E-Dioclass media is declared valid, practical.